Association of Body Mass, Serum Insulin, and Lipid Profile with Serum Melatonin Levels in Individuals in Babylon, Iraq - Anwar Kawther Ali; Ekhlas Hatem Abd_Alameer; Qais Ismaeel Kadhem (Medical Journal of Babylon)
Background: Melatonin has been shown to directly affect metabolism and body weight management, in addition to its established involvement in circadian rhythm. Objectives: We aimed to investigate the relationship between serum melatonin and adult BMI, serum insulin, and lipid profile (cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and TG). Materials and Methods: In this cross-sectional study, 150 individuals (78 females and 72 males) aged 18–60 were recruited. Samples were collected at Imam al-Sadiq Hospital and Marjan Hospital in Babylon Governorate from September 1, 2023, to June 30, 2024. Patients’ metabolic blood parameters, such as insulin, triglycerides, HDL, LDL, HB, urea, creatinine, and cholesterol, were measured and their association with serum melatonin determined. Results: This study included a total of (150) patients, with the mean age of participants (32.0 ± 7.9) years and a median age of (31) years. Regarding gender distribution, the proportion of female patients was 52.0% compared to males (48.0%). Mean BMI of study patients was (30.6 ± 8.3) kg/m2. The majority (60.7%) of patients were obese (BMI ≥ 30). There was a significant difference among age groups, with a P value of 0.006. Comparison between males and females regarding serum melatonin level indicated that there were no significant differences between them. In a similar manner, no significant difference was observed between urban residents (11.7 ± 11.7) and rural residents (26.9 ± 10.7). Conclusion: A correlation was observed between insulin resistance and melatonin secretion; groups with elevated BMI with higher melatonin levels also had higher insulin resistance. Also, higher melatonin concentrations in the serum, insulin excess (overweight), and a high lipid profile, along with low vitamin D, were observed. The high BMI group has low vitamin D, whereas normal BMI group has normal vitamin D. Thus, overweight (high BMI) people tend to have lower vitamin D levels.